Pembaharuan Sistem Pendidikan di Pesantren: (Studi Kasus di Pondok Pesantren An-Nur Rejosari, Pakis, Magelang) (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2019)
The education system includes several interrelated components. The education system in pesantren usually applies as it is, especially for salaf pesantren in teaching the yellow book. The success of santri education - the learning of the yellow book - in pesantren depends on the existing education system in pesantren, regardless of baraka values. Along with the development of the times inevitably pesantren must also make a system update, one of them is by developing an existing education system to improve the quality of graduates produced. An-Nur boarding school is developing include clear educational objectives and systems, the best alumni become instructors, students from various backgrounds, practical teaching methods, focus on nahw and sharf science, audio visual as a learning tool. This is supported by a representative place (cool environment), facilities and infrastructure, as well as professional teachers. While the obstacles related to administrative issues for foreign students are also in language limitations and age diversity. This shows that An-Nur's pesantren in developing the education system to improve the quality of graduates uses an acceleration system in the teaching of the yellow book.